The Safety of Low-Dose Aspirin on the Mode of Delivery: Secondary Analysis of the Effect of Aspirin in Gestation and Reproduction Randomized Controlled Trial - Eubanks, Allison A.; Nobles, Carrie J.; Mumford, Sunni L.; Kim, Keewan; Hill, Micah J.; Decherney, Alan H.; Sjaarda, Lindsey A.; Ye, Aijun; Radoc, Jeannie G.; Perkins, Neil J.; Silver, Robert M.; Schisterman, Enrique F. (American Journal of Perinatology, 2020)
Objective This study aimed to examine whether prenatal low-dose aspirin (LDA) therapy affects risk of cesarean versus vaginal delivery.Study Design This study is a secondary analysis of the randomized clinical effects of aspirin in gestation and reproduction (EAGeR) trial. Women received 81-mg daily aspirin or placebo from preconception to 36 weeks of gestation. Mode of delivery and obstetric complications were abstracted from records. Log-binomial regression models estimated relative risk (RR) of cesarean versus vaginal delivery. Data were analyzed among the total preconception cohort, as well as restricted to women who had a live birth.Results Among 1,228 women, 597 had a live birth. In the intent-to-treat analysis, preconception-initiated LDA was not associated with risk of cesarean (RR = 1.02; 95% confidence interval [CI]: 0.98–1.07) compared with placebo. Findings were similar in just women with a live birth and when accounting prior cesarean delivery and parity.Conclusion Preconception-initiated daily LDA was not associated with mode of delivery among women with one to two prior losses.Key Points
Keywords: low-dose aspirin; spontaneous vaginal delivery; cesarean delivery; induction; placentation